Инструменты управления валютными рисками предприятий нефинансового сектора - Дорошенко, А. А. (НТУ "ХПИ", 2013)
Неопределенность валютного курса в будущем может стать причиной значительных денежных потерь любого субъекта хозяйствования (предприятия, компании, банка), вероятность этого отражается понятием "валютный риск". Причиной валютных рисков может стать изменение как политических так и экономических факторов. В современных условиях валютные риски влияют на результаты хозяйственной деятельности многих учреждений, даже если их деятельность прямо не связана с осуществлением внешнеэкономических операций. Учитывая это особое значение, приобретает поиск методов управления валютно-конверсионными рисками предприятий с целью снижения вероятных денежных расходов или уклонения от рисковой ситуации в случае неблагоприятных колебаний валютного курса

Due to globalization tendency of the world economy, activities of any company in any form involve a great number of risks. However, their significant increase is typical for companies carrying out foreign economic activity as they are affected not only by internal environment factors, but also by external ones. The strategy of managing currency risks should comprise the following elements: taking all possible measures to avoid risks which lead to significant losses; controlling the risk and minimizing amounts of eventual losses if tt is impossible to completely avoid it, assigning the currency risk in case it is impossible to avoid it. After assessing the risk probability, degree, and value, the company selects the appropriate method of minimizing the currency risk. In routine management of foreign economic activity such methods are normally subdivided into “internal” and “external”. The former are measures to avert the emergence of risk and are thus preventive in nature. The “external” methods mainly affect not the process of emergence of risk, but its consequences by way of their elimination
Keywords: стратегия управления; хеджирование; внутренние и внешние инструменты; срочные сделки; currency risk; management; minimization; hedging; strategy